Young Canadian e-Cigarette Users and the COVID-19 Pandemic: Examining Vaping Behaviors by Pandemic Onset and Gender - Hopkins, D. Brett; Al-Hamdani, Mohammed (Frontiers in Public Health, 2021)
The aim of this study was to test how youth and young adult e-cigarette users behaviours responded to the COVID-19 pandemic. The 2020 Youth and Young Adult Vaping Survey (N = 1308) included 540 (44.7%) participants that reported differences in their vaping behaviours since the onset of the pandemic. Gender was the only relevant covariate that yielded a significant effect and/or interaction through a multivariate test. A two-way multivariate analysis of variance was used to test the effect of pandemic onset (pre- versus during-pandemic), gender (males versus females), and their interaction on vaping behaviours (number of vaped days per week, vaped episodes per day, and puffs per vaping episode). Respondents reported fewer days of vaping per week, episodes of vaping per day, and puffs per vaping episode during-pandemic than pre-pandemic [F(3, 533) = 52.81, p < .001, ηp2 = .229]. The multivariate effect of gender on the three vaping outcomes was not statistically significant [F(3, 533) = 2.14, p = .095, ηp2 = .012], though the interaction between pandemic onset and gender was [F(3, 533) = 2.86, p = .036, ηp2 = .016]. Males reported fewer episodes of vaping per day [t(262) = 7.40, p < .001, 95% CI: 5.19 - 8.97] and puffs per vaping episode [t(263) = 3.23, p = .001, 95% CI: .292 - 1.20] during-pandemic than pre-pandemic. Females reported fewer vaping episodes per day during-pandemic than pre-pandemic [t(273) = 5.14, p < .001, 95% CI: 2.76 - 6.18]. Further, females reported more frequent puffs per vaping episode in comparison to males during-pandemic [t(538) = -2.38, p = .017, 95% CI: -2.09 - -.200]. The COVID-19 pandemic presents an opportunity to reduce vaping through health promotion messaging. Since females take more puffs per vaping episode overall, they may benefit the most from greater vaping cessation supports.